Respuesta :

Answer:

1/2

Step-by-step explanation:

1/3 + 1/6

LCM of 3 and 6 is 6.

therefore, multiple the fraction that doesn't have 6 as denominator with a fraction that makes the denominator equal to the LCM.

1/3 × 2/2 = 2/6

(we have used 2/2 because 3×2= 6)

so,

2/6+1/6 = 2+1/6

(2 + 1 whole divided by 6)

therefore we get,

3/6

on simplification,

3/6 = 1/2 = 0.5

hope it helps!!

PLEASE MARK BRAINLIEST..

Answer:

1/3 + 1/6 = 2/6 + 1/6 = 1/2 (simplified from 3/6)

Step-by-step explanation:

since 1/3 = 2/6 (to get the same denominator)

2/6 + 1/6 = 3/6 (or 1/2 simplified, when divided by 3/3)

so 2/6 + 1/6 = 3/6

2 is the first blank

1/2 is your answer. (second blank)

hope this helps:)